The law of expansion of the universe: translation of Georges Lemaître's seminal article - Fábris, Júlio César; Piattella, Oliver (Cadernos de Astronomia, 2024)
The translation of Georges Lemaître's 1927 article is presented, which proposed the law that relates the speed of cosmic recession of galaxies with their distance from us, the Hubble-Lemaître law.
Keywords: Georges Lemaître; Hubble-Lemaître law; expansion of the universe